Do, say, learn: the functions of mothers' speech to infants. Issue 1 (22nd January 2020) - KUCHIRKO, Yana A.; SCHATZ, Jacob L.; FLETCHER, Katelyn K.; TAMIS-LEMONDA, Catherine S.
Abstract: We examined the functions of mothers' speech to infants during two tasks – book-sharing and bead-stringing – in low-income, ethnically diverse families. Mexican, Dominican, and African American mothers and their infants were video-recorded sharing wordless books and toy beads in the home when infants were aged 1;2 and 2;0. Mothers' utterances were classified into seven categories (labels/descriptions, emotion/state language, attention directives, action directives, prohibitions, questions, and vocal elicitations) which were grouped into three broad language functions: referential language, regulatory language, and vocalization prompts. Mothers' ethnicity, years of education, years living in the United States, and infant sex and age related to mothers' language functions. Dominican and Mexican mothers were more likely to use regulatory language than were African American mothers, and African American mothers were more likely to use vocalization prompts than were Latina mothers. Vocalization prompts and referential language increased with mothers' education and Latina mothers' years living in the United States. Finally, mothers of boys used more regulatory language than did mothers of girls. Socio-cultural and developmental contexts shape the pragmatics of mothers' language to infants.